A Pair of NiCo2O4 and V2O5 Nanowires Directly Grown on Carbon Fabric for Highly Bendable Lithium‐Ion Batteries. Issue 18 (18th March 2019) - Son, Ji‐Myeong; Oh, Saewoong; Bae, Seok‐Hu; Nam, Sanghee; Oh, Il‐Kwon
Abstract: Mechanically bendable and flexible functionalities are urgently required for next‐generation battery systems that will be included in soft and wearable electronics, active sportswear, and origami‐based deployable space structures. However, it is very difficult to synthesize anode and cathode electrodes that have high energy density and structural reliability under large bending deformation. Here, vanadium oxide (V2 O5 ) and nickel cobalt oxide (NiCo2 O4 ) nanowire‐carbon fabric electrodes for highly flexible and bendable lithium ion batteries are reported. The vanadium oxide and nickel cobalt oxide nanowires were directly grown on plasma‐treated carbon fabric and were used as cathode and anode electrodes in a full cell lithium ion battery. Most importantly, a pre‐lithiation process was added to the nickel cobalt oxide nanowire anode to facilitate the construction of a full cell using symmetrically‐architectured nanowire‐carbon fabric electrodes. The highly bendable full cell based on poly(ethylene oxide) polymer electrolyte and room temperature ionic liquid shows high energy density of 364.2 Wh kg −1 at power density of 240 W kg −1, without significant performance degradation even under large bending deformations. These results show that vanadium oxide and lithiated nickel cobalt oxide nanowire‐carbon fabrics are a good combination for binder‐free electrodes in highly flexible lithium‐ion batteries. Abstract : High capacity vanadium oxide nanowires and pre‐lithiated nickel cobalt oxide nanowires, each on carbon fibers, make a pair of full cell electrodes a with poly(ethylene oxide)‐based electrolyte, facilitating a high energy density flexible lithium‐ion battery. The full cell battery manifests stable capacity in large bending states, resolving safety issues in liquid‐electrolyte lithium‐ion batteries.